PENGARUH KEBISINGAN DAN GETARAN MESIN PADA KESEHATAN KERJA TERHADAP KINERJA PRAJURIT PENGAWAK KRI - Darda, Abu; Arie Kurniawan, Eko; Irfan Ilmi, Muhammad; Munajat Nurhartonosuro, Imam (Pascasarjana UDA, 2024)
Noise and engine vibration on the Republic of Indonesia Ship (KRI) can significantly affect the health and performance of soldiers. In the context of the warship work environment, these two factors have the potential to cause hearing loss, musculoskeletal problems, and decreased productivity and operational effectiveness. Therefore, it is important to understand the impact of noise and vibration exposure on the health and performance of soldiers. This study aims to analyze the effect of engine noise and vibration on the occupational health and performance of KRI crew soldiers, as well as to evaluate the effectiveness of the mitigation measures implemented. The study used a quantitative approach involving 50 KRI soldier respondents selected through stratified random sampling techniques. Data were collected through noise and vibration measurements, questionnaires, interviews, and medical record analysis. Validity and reliability tests showed that the research instrument was valid and reliable, with Cronbach's Alpha between 0.80 and 0.88. Data analysis was carried out using linear regression, correlation analysis, and regression coefficient tests. The linear regression results show that engine noise has an unstandardized regression coefficient of 0.45 (t = 3.75, p = 0.001), and engine vibration has an unstandardized regression coefficient of 0.60 (t = 4.00, p = 0.000) on occupational health. For soldier performance, engine noise has an unstandardized regression coefficient of -0.25 (t = -2.50, p = 0.015), and engine vibration has an unstandardized regression coefficient of -0.35 (t = -2.50, p = 0.016). The regression coefficient test shows an F value for occupational health of 15.60 (p = 0.000) and for soldier performance of 18.75 (p = 0.000), indicating the significance of the overall model. Engine noise and vibration have a significant impact on the health and performance of KRI soldiers, emphasizing the need for effective mitigation measures to manage these two factors. The results of this study provide important information for improving working conditions and increasing operational effectiveness on warships.